Spinal cord atrophy correlates with disease duration and severity in amyotrophic lateral sclerosis. Issue 1 (March 2014) - Branco, Lucas M. T.; De Albuquerque, Milena; De Andrade, Helen Maia T.; Bergo, Felipe P. G.; Nucci, Anamarli; França, Marcondes C.
Abstract Our objective was to investigate spinal cord (SC) atrophy in amyotrophic lateral sclerosis (ALS) patients, and to determine whether it correlates with clinical parameters. Forty-three patients with ALS (25 males) and 43 age- and gender-matched healthy controls underwent MRI on a 3T scanner. We used T1-weighted 3D images covering the whole brain and the cervical SC to estimate cervical SC area and eccentricity at C2/C3 level using validated software (SpineSeg). Disease severity was quantified with the ALSFRS-R and ALS Severity scores. SC areas of patients and controls were compared with a Mann-Whitney test. We used linear regression to investigate association between SC area and clinical parameters. Results showed that mean age of patients and disease duration were 53.1 ± 12.2 years and 34.0 ± 29.8 months, respectively. The two groups were significantly different regarding SC areas (67.8 ± 6.8 mm² vs. 59.5 ± 8.4 mm², p < 0.001). Eccentricity values were similar in both groups (p = 0.394). SC areas correlated with disease duration (r = − 0.585, p < 0.001), ALSFRS-R score (r = 0.309, p = 0.044) and ALS Severity scale (r = 0.347, p = 0.022). In conclusion, patients with ALS have SC atrophy, but no flattening. In addition, SC areas correlated with disease duration and functional status. These data suggest that quantitative MRI of the SC may be a useful biomarker in the disease.